(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Ancient scripts in South-western Iberia are normally carved in local stone and usually have a stelae shape. Although this particularity is not confirmed in all cases, it seems clear that this was verified in the most part, associating functionally to funerary contexts. These monuments, which mark sepulchral spaces, constitute a very peculiar element of these spaces and introduce them into a figurative reality which is analysed here. In rare cases, the monuments are historicized, combining writing with little complex representations, whose interpretation sometimes provokes some controversy. But the texts themselves, in their configuration, distribution in the support and framing, construct an image that presents itself as a relevant figurative element. The different strategies used by the producers of these monuments are also examined in this contribution.